Conséquences génétiques de la production de larves d'huîtres en écloserie : étude des processus de dérive et de sélection - Taris, Nicolas; Sauvage, Christopher; Batista, Frederico; Baron, Sophie; Ernande, Bruno; Haffray, Pierrick; Boudry, Pierre (Actes du 6e colloque national BRG, La Rochelle, 2-3-4 octobre 2006, 2006)
Previous studies have shown heritable variation in larval developmental traits in the Pacific oyster Crassostrea gigas. In order to study the genetic consequences of production of oyster larvae in hatcheries, two factors, specific to hatcheries, were examined: the effect of discarding the smallest larvae (i.e. culling) and the effect of temperature (20°C versus 26°C). A mixed-family approach was used in order to infer the genetic composition of larval populations and family assignment, limiting possible environmental bias and allowing the study of a relatively large number of families using a limited number of larval tanks. Our results show that three multiplexed highly polymorphic microsatellite markers are a powerful tool for family assignment and, consequently, for the study of bivalve larvae genetics. Culling, by selective sieving of the smallest larvae is an advantageous practice at a phenotypic scale as it reduced variance in larval size, variance of developmental rate and time to settlement. Culling of 50% of the larval population only led to 15% less spat, showing a positive phenotypic correlation between larval growth and settlement success. However, culling represents a substantial risk for diversity loss, because it increases the variance of reproductive success among parental oysters. The effective population sizes of early settling cohorts of settlement were lower than those of later ones. Our results show that the settlement of slow growing larvae significantly contributes to minimizing the variability of reproductive success and therefore to maximizing genetic diversity. These results corroborate the low estimations of variability of broodstocks sampled in several French commercial hatcheries, relative to natural populations. The genetic composition of the larval population and the resulting spat was significantly different between the two tested temperatures, revealing genotype x environment interaction for survival. Similarly, genotype x environment interaction was also observed for larval ...